Urgensi Bimbingan Kolaboratif bagi Anak yang Mengalami Learning Disabilities di Sekolah Dasar - Medina Chodijah (Syifa al-Qulub, 2017)
Learning disabilities is a wide variety of learning problem which is known more than 100 years ago. No one can help learming disabled children alone.Collaborate  is the best way that can maximize they potential and minimize they problems. Many research was conduct to see the effect of the collaborative guidance, and the result shown that collaborative has positif effect to  all children aspects. But in Indonesia there still no structurize platform to conduct the collaborative guidance.